(untitled) (Journal of Asian Development Studies, 2024)
Child sexual abuseis a pressing issue that poses a grave threat to the well-being of children. The UNCRC recognizes the role of provoking awareness, knowledge, and information. However, concerns about the ethical considerations remain there. Recent incidents of child incest and pornography have sparked debates. This research paper focuses on the portrayal of child sexual abuse in electronic media and its impact on parents’ awareness’ knowledge, and information. The study aims to investigate the disparitiesbetween parents who watch HUM TV and private news channels in terms of their understanding of child sexual abuse. The study is conducted in Muzaffargarh and Islamabad; quantitative and qualitative methods are utilized, including surveys, group discussions, and interviews with various stakeholders. The researcher used cultivation theory to accomplish this study. For data analysis, SPSS was used to perform a descriptive analysis method to find out the outcomes of the reported question. The study finds a 95% confidence interval and 5% margin of error and collected an additional 10% sample to account for attrition, while stratified random sampling is employed. Results of this study show that 63% of male parents and 53% of female parents used TV as the primary source of information about child sexual abuse. 38% of male parents and 11% of female parents use news media, and 32% of male parents and 84% of female parents use entertainment media as their primary source of awareness about child sexual abuse. The findings from this study will contribute to the existing literature by providing empirical evidence of the impact of media coverage on parental awareness and understanding of child sexual abuse.